Central Injection of Glucose Modifies Behavior, Amino Acid and Monoamine Metabolism in Neonatal Chicks under Acute Stressful Conditions - Yumi Ogino; Junki Yoshida; Asako Shigemura; Masakazu Yamanaga; D. Michael Denbow; Mitsuhiro Furuse (The Journal of Poultry Science, 2016)
The effect of intracerebroventricular (i.c.v.) injection of a wide range of glucose concentrations on the behavioral response, central amino acid and monoamine contents was investigated in chicks exposed to a social isolation stressful condition. The chicks were given an i.c.v. injection of 0.21, 0.42, 0.84, and 1.68 μmol of D-glucose, and then behavioral changes were observed over 10 min. The behavioral stress response was dose-dependently decreased and calm behavior was increased by i.c.v. administration of glucose. In the diencephalon, glutamine was positively correlated, whereas glycine was negatively correlated with the dose of glucose. In the telencephalon, the dopamine metabolite and dopamine turnover rates were positively correlated, whereas dopamine was negatively correlated with doses of glucose. In the plasma, isoleucine and hydroxyproline were positively correlated with the dose of glucose, and several amino acids were also influenced by glucose levels.These results suggest that the possible pathways of the sedative effect of glucose include: (1) amino acids synthesized from injected glucose, which can induce the sedative and/or hypnotic effects; (2) amino acids modified by injected glucose transported in the brain from the peripheral tissues; and (3) injected glucose-induced decreases in brain dopamine levels. In conclusion, these changes induced by central glucose interact and induce the sedative effect in neonatal chicks.